2018
DOI: 10.1186/s13104-018-3603-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of clients satisfaction with outpatient services at Yekatit 12 Hospital Medical College, Addis Ababa, Ethiopia

Abstract: ObjectiveThis study aimed at assessing clients’ satisfaction and associated factors among adults. A cross sectional facility based study was conducted on 420 clients of Yekatit 12 Hospital Medical College from 1 June 2016 to 1 July 2016. Data was entered, cleaned, and analyzed using SPSS statistical package. Data was analyzed using a multivariable logistic regression model to find out the most significant predictors for clients satisfaction with outpatient services at Yekatit 12 Hospital Medical College.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
20
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 13 publications
8
20
7
Order By: Relevance
“…This finding was comparable with Bahirdar Felege Hiwot Referral Hospital study (57.8%) [8]. The current satisfaction level was slightly higher than the Yekatit 12 Referral Hospital study (47%) [9] and slightly lower than the studies in Wolita Sodo teaching hospital (54.2%) [10] and Jimma (57.1%) [11]. In contrast to the current study and the above-cited references in the country, the nationwide survey reported an overall patient satisfaction of 74.5% [2].…”
Section: Discussionsupporting
confidence: 79%
“…This finding was comparable with Bahirdar Felege Hiwot Referral Hospital study (57.8%) [8]. The current satisfaction level was slightly higher than the Yekatit 12 Referral Hospital study (47%) [9] and slightly lower than the studies in Wolita Sodo teaching hospital (54.2%) [10] and Jimma (57.1%) [11]. In contrast to the current study and the above-cited references in the country, the nationwide survey reported an overall patient satisfaction of 74.5% [2].…”
Section: Discussionsupporting
confidence: 79%
“…21,22 In this study, the presence or absence of a sign and direction indicators were significantly associated with patient satisfaction. It is consistent with the studies conducted in Addis Abeba, Yekatit 12 hospital, 42 where the availability of sign and diction indicator increases patient satisfaction by 98% and in Bahirdar, Ethiopia, 43 in which 74% of patients dissatisfied due to the absence of sign and direction indicators. The provision of sign and direction indicators in the healthcare facilities may provide a good image for customers to access easily the room they need for healthcare services.…”
supporting
confidence: 90%
“…41 Patients who got some ordered drugs from the health facility were 3.7 times more likely satisfied than those who did not get any ordered drugs from the health facilities. It is in agreement with the studies done in Addis Abeba public hospitals, 41 Yekatit 12 medical college, 42 Jimma University specialized hospital, 31 Iluababor zone, 32 Wolayita-Sodo, 36 Dabraberhan, 35 and Bahardir, Ethiopia 43 where patients who did not get drugs were less satisfied than those who had ordered drugs.…”
supporting
confidence: 89%
“…In Ethiopia, few reports of previously published data described the extent and factors associated with the quality of health or pharmaceutical services ( Oljira and Gebre-Selassie, 2001 ; Tateke et al, 2012 ; Surur et al, 2015 ; Woldeyohanes et al, 2015 ; Workye et al, 2015 ; Abdosh, 2016 ; Kefale et al, 2016 ; Berehe et al, 2018 ). To our knowledge, none of the published data have directly addressed the degree and reasons for dissatisfaction/satisfaction from outpatients with pharmacy services.…”
Section: Introductionmentioning
confidence: 99%